Scanning Ion Probe Studies of Silicon Implantation Profiles in AlGaN/GaN HEMT Heterostructures - Kocan, M.; Umana-Membreno, G.; Kilburn, M.; Fletcher, Ian; Recht, F.; McCarthy, L.; Mishra, U.; Nener, B.; Parish, G. (Springer, 2008)
This paper reports results of scanning ion probe studies fo silicon implantation profiles in source and drain regions of AlGaN/GaN high-electron-mobility transistor (HEMT) heterostructures. It is shown that both the undoped channel length and the transition region between implanted and non-implanted regions become wider with increasing depth in the structure. These results may explain the previously reported existence of resistance associated with the transition region between implanted and non-implanted semiconductor regions in AlGaN/GaN HEMT heterostructures with non-alloyed Si-implanted source and drain ohmic contact regions.